Perceptions of Prospective Physics Teachers on the Application of Statistics in Education - Aviyanti, Lina; Janeusse Fratiwi, Nuzulira (Ridwan Institute, 2024)
The Application of Statistics in Education (ASE) course is one of the courses attended by pre-service physics teachers to enable them deal with research data using statistical analysis. This study aims to analyse students' perceptions of the ASE material prior to attending the lectures. The research method employed is descriptive quantitative. The research sample consists of 37 students in the Physics Education study program who are taking the ASE course. Data were collected through the Student Perception towards Statistics Questionnaire (SPSQ) instrument, which comprises 40 statements with four Likert scale rating criteria: Strongly Agree, Agree, Disagree, and Strongly Disagree. The data were analysed using Rasch modeling, specifically Wright Map Analysis, to map participant perceptions, while the percentage agreement of participants was analysed based on four aspects of the SPSQ questionnaire. The results of the average percentage analysis of participants’ agreement for each aspect are: (1) attitude towards Statistics at 97.3%, categorized as very good, (2) the importance of Statistics in daily life and profession at 97.3%, categorized as very good, (3) the ability to process statistical data using data analytics tools at 37.84%, categorized as poor, and (4) the ability to apply Statistics in education at 8.8%, categorized as very poor. Furthermore, the Wright Map Analysis indicates that all participants had a favorable attitude and were eager to learn more about how statistics are implemented in education. They agreed that it is critical to master and be able to apply advanced statistics techniques in educational and research contexts.